PENGEMBANGAN MEDIA EVALUASI PEMBELAJARAN BERBASIS GAME INTERNET EDUCANDY SEBAGAI SARANA PEMBELAJARAN DARING - Miftahul Mufid; Ahmad Farid Utsman (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
In the era of the pandemic, schools are required to carry out online learning. This resulted in the development of an online-based Arabic learning evaluation to be made. The purpose of this research is to develop an online-based learning evaluation media using the educandy platform and test it on class X MA Sunatunnut Senori Tuban students. This research uses the Borg and Gall R&D method. The research shows the results that the average score from the aspects of usability, display, interactive and learning shows the results of 3.25% this value is in the good category so it can be concluded that this Arabic learning evaluation media can be used as online media and is able to provide benefits. to class X MA Sunatunnur Senori Tuban as an independent learning medium.